Causes of Teacher Shortage in Private Schools: Implications for Human Resource Managers in Ilorin Metropolis - FAMAYE, Esther Oluwayemisi; OBE, Emmanuel Olusola (International Journal of Educational Management, 2025)
This study ascertain the causes of teacher shortage in Private schools in Ilorin Metropolis. The population of the study comprised all the school heads in Ilorin Metropolis. The target population was 1,370 private school head teachers and 411 were sampled using stratified random sampling for both primary and secondary. Three research questions were raised to guide the study. A 15 item questionnaire was used to elicit responses from school head teachers in Ilorin Metropolis. The research questions were answered using mean and percentage. The respondents agreed that most of the items listed such as irregular payment of salary and lack of motivation were causes of teacher shortage in Private schools in Ilorin Metropolis. The researcher concluded that adequate welfare package, remuneration and motivation will assist in reinforcement of teachers confidence in private schools and it was recommended that school human resource managers should make provision for staff pension.